Adverse effects and underlying mechanism of amorphous silica nanoparticles in liver. (January 2023) - Liang, Qingqing; Sun, Mengqi; Ma, Yuexiao; Wang, Fenghong; Sun, Zhiwei; Duan, Junchao
Abstract: Amorphous silica nanoparticles (SiNPs) have been widely used and mass-producted due to its unique properties. With the life cycle of SiNPs-based products, SiNPs are further released into the air, soil, surface water and sediment, resulting in an increasing risk to humans. SiNPs could enter into the human body through vein, respiratory tract, digestive tract or skin. Moreover, recent evidences have showed that, regardless of exposure pathways, SiNPs could even be traced in liver, which is gradually considered as one of the main organs that SiNPs accumulate. Increasing evidences supported the link between SiNPs exposure and adverse liver effects. However, the research models are diverse and the molecular mechanisms have not been well integrated. In this review, the liver-related studies of SiNPs in vivo and in vitro were screened from the PubMed database by systematic retrieval method. We explored the interaction between SiNPs and the liver, and especially proposed a framework of SiNPs-caused liver toxicity, considering AOP Wiki and existing studies. We identified increased reactive oxygen species (ROS) as a molecular initiating event (MIE), oxidative stress, endoplasmic reticulum stress, lysosome disruption and mitochondrial dysfunction as subsequent key events (KEs), which gradually led to adverse outcomes (AOs) containing liver dysfunction and liver fibrosis through a series of key events about cell inflammation and death such as hepatocyte apoptosis/pyroptosis, hepatocyte autophagy dysfuncton and hepatic macrophages pyroptosis. To our best knowledge, this is the first AOP proposed on SiNPs-related liver toxicity. In the future, more epidemiological studies need to be performed and more biomarkers need to be explored to improve the AOP framework for SiNPs-associated liver toxicity. Graphical abstract: Image 1 Highlights: The AOP framework was used for the first time to integrate the evidences of SiNPs-related liver toxicity mechanism. Increased ROS is a molecular initiation event linking SiNPs and adverse effects in liver. Cell death and inflammation play a key role in SiNPs-related hepatotoxicity. The adverse outcomes of SiNPs in liver are mainly included hepatic dysfunction and fibrosis.